The Little Book of Results : a Quick Guide to Better Performance and Greater Results in Life. - Smart, Jamie (John Wiley & Sons, Incorporated, 2018)
' It is easier to complicate than to simplify' - this book takes up that challenge and aims to refine and clarify the theories in the original Results to produce a more succinct route to clarity and better results for the reader - because we all want to see results at home, at work and in life! Using transformational coaching techniques, examples, exercises and metaphors, Jamie talks the reader through the three key changes they need to achieve the results they are after and inspire others to do the same. Based on the principles of The Clarity Coaching Model, the reader will learn how to de-congest their mind to think more clearly, make better decisions and improve performance - achieving the 'flow' state attributed to the results of top-flight individuals. Clearer thinking removes the stress and anxiety from decision making and allows you to focus on your goals. Rather than a step-by-step process, the reader is encouraged to form a deep understanding of themselves to awaken their inner potential and improve their innate abilities including better listening, deeper connections, more motivation and greater innovation and creativity.